Performance and physiological responses to repeated-sprint exercise: a novel multiple-set approach - Serpiello, F. R.; McKenna, M. J.; Stepto, N. K.; Bishop, D. J.; Aughey, R. J. (European Journal of Applied Physiology, 2011)
We investigated the acute and chronic responses to multiple sets of repeated-sprint exercise (RSE), focusing on changes in acceleration, intermittent running capacity and physiological responses. Ten healthy young adults (7 males, 3 females) performed an incremental test, a Yo-Yo intermittent recovery test level1 (Yo-Yo IR1), and one session of RSE. RSE comprised three sets of 5 × 4-s maximal sprints on a non-motorised treadmill, with 20 s of passive recovery between repetitions and 4.5 min of passive recovery between sets. After ten repeated-sprint training sessions, participants repeated all tests. During RSE, performance was determined by measuring acceleration, mean and peak power/velocity. Recovery heart rate (HR), HR variability, and finger-tip capillary lactate concentration ([Lac-]) were measured. Performance progressively decreased across the three sets of RSE, with the indices of repeated-sprint ability being impaired to a different extent before and after training. Training induced a significant increase (p < 0.05) in all indices of performance, particularly acceleration (21.9, 14.7 and 15.2% during sets 1, 2 and 3, respectively). Training significantly increased Yo-Yo IR1 performance by 8% and decreased ?[Lac-]/work ratio (-15.2, -15.5, -9.4% during sets 1, 2 and 3, respectively) and recovery HR during RSE. There were strong correlations between Yo-Yo IR1 performance and indices of RSE performance, especially acceleration post-training (r = 0.88, p = 0.004). Repeated-sprint training, comprising only 10 min of exercise overall, effectively improved performance during multiple-set RSE. This exercise model better reflects team-sport activities than single-set RSE. The rapid training-induced improvement in acceleration, quantified here for the first time, has wide applications for professional and recreational sport activities.